PERMASALAHAN-PERMASALAHAN YANG DIHADAPI SEKOLAH PENYELENGGARA PENDIDIKAN INKLUSI PADA TINGKAT SD - Tarnoto, Nissa (HUMANITAS, 2016)
AbstractThe declaration of inclusive education that focus to facilitate the educational needs of children with special needs (ABK) has been running in many area in Indonesia, especially in big cities such as Jakarta, Yogyakarta, Surabaya, Malang. However, many problems rose for it’s implementation. This study aims to determine the problems experienced by the teachers and schools using qualitative metode and indigenous approach that involved 112 teachers from 18 inclusive schools in Yogyakarta as subjects. Data was collected through open ended questionnaire and was analyzed by coding techniques. The results showeda wide range of problems faced by the teachers and schools such as lack of competence in dealing with students with special needs, lack of parental awareness of children with special needs, the number of students with special needs in every class, lack of cooperation of various parties such as professional government and soceity.Keyword: children with special needs, inclusion education, indigenous psychology